Communicating personalized risk of diabetes and offering weight reduction program choice: Recruitment, participation, and outcomes. Issue 5 (May 2021) - Bailey-Davis, Lisa; Wood, G. Craig; Cook, Adam; Cunningham, Krystal; Jamieson, Scott; Mowery, Jacob; Naylor, Allison; Rolston, David D.; Seiler, Christopher; Still, Christopher D.
Highlights: Few persons with prediabetes are aware of risk. Communication of personalized risk and weight loss to reduce risk is feasible. Response rate is better than expected from recruitment letters. Remote-delivered lifestyle interventions with registered dietitian frequently chosen. Significant improvements in key health outcomes sustained at 12 months. Abstract: Objective: Low patient recruitment into diabetes prevention programs is a challenge. The primary aim of this study was to demonstrate that an increased recruitment rate can be achieved by communicating personalized risk of progression to type 2 diabetes, estimating risk reduction with weight loss, and offering program choice. Secondary aims included program participation rate, weight loss, and short-term decreased diabetes risk. Methods: In this single-arm study, persons with prediabetes from 3 primary care sites received a letter that communicated their personalized risk of progression to diabetes within 3-years, estimated risk reduction with 5, 10, 15 % weight loss, reported in pounds, and offered a choice of 5 free, 6-month, programs. A one-sided test was used to compare the recruitment rate against the maximum expected rate of (10 %). Results: Recruitment response rate was 25.3 % (81/328, 95 % CI=[20.0 %, 29.4 %]) which was significantly higher than expected (p < 0.0001). Overall, 65 % of participants completed >75 % of contacts. BMI, HbA1c, and diabetes risk (all p < 0.0001) improved at 6 months; BMI (p < 0.0001) and HbA1c (p < 0.05) improved at 12 months. Conclusion: Recruitment response rate was better than expected. Practice implications: Communicating personalized risk and reduction estimates with a choice of programs resulted in favorable outcomes, sustained at 1-year.